Identification of ergonomics risk factor and work-related psychosocial using DOSH risk assessment on backpack leaf blower workers / Amy Zuria Abdul Ajid - Amy Zuria, Abdul Ajid (2021)
Cleaning industry is one of the main sectors that supports national economic growth and cleanliness is an essential element in healthy living. Ergonomic, health and safety awareness is important to make sure the industry excel. There are many type of cleaning service involve in this industry but this study only focus on cleaning workers who uses backpack leaf blower machine. The usage of backpack leaf blower is very popular in cleaning industry because it is time-saving, efficient and mobile. Objective of this study is to identify worker’s body part with the experience of ache, pain and discomfort among backpack leaf blower workers. This study also was conducted to assess physical risk factor and psychosocial work factor that causes back pain and body discomfort to backpack leaf blower workers. Ten respondents who works as cleaner in one of a local university was analysed using Ergonomic Risk Assessment (ERA) which was adapted from Guidelines on Ergonomic Risk Assessment at Workplace 2017 by DOSH Malaysia to determine ergonomic risk level of the employees. From the analysis conducted and calculation of Total discomfort score, body parts which are at risk for injury and discomfort on female workers are wrist (right hand) with scores of 20.98%, lower back (18.17%), legs (13%) and shoulders (12.19%). Male workers on the other hand shows that, the body parts with high risk of injury and discomfort is on the shoulders (20.81%) followed by neck (17.59%), right wrist with 17.24% and lower back (16.29%). Factors contribute to risk of injury and discomforts are awkward posture (head bending forward, twisted torso and wrists in flexion position), repetitive motion (uses of hands, fingers, wrists and shoulders intensively), vibration (on hands and all over body) and load carrying activities (working with loads on the back for a long walking distance). From psychosocial aspect lack management control in work schedule rotation, heavy workload, long working hours and management failure are main caused. Employers are responsible to create awareness about ergonomic besides creating procedures and safe work practices which can lessen the pain and discomfort to the workers.